FEMINIST PERSPECTIVE IN LAUREN WEISBERGER’S THE DEVIL WEARS PRADA - Bayu Andika Prasatyo (STKIP PGRI Jombang, 2018)
Novel becomes the exciting entertainment that everyone can enjoy. Within the novel the writer can analyze the part of both intrinsic and extrinsic. In this research the writer analyzes the feminist perspective in the Devil Wears Prada by Lauren Weisberger. The writer takes Miranda Priestly character as a viewing of feminist perspective in this modern era. The research is conducted to find out the characters and characterization and feminist perspective of Miranda Priestly. In analyzing the research, the writer uses feminist approach to analyze about women. Besides, the writer also uses library research which are the novel itself and some books or journal that can be found in the internet related to the character, characterization and feminism. There are nine characterization of Miranda Priestly shown in the analysis. The characterization that the writer analyzes are Jewish, Fashionable, Hectic, Demand, Power, Influence, Discriminate, Smart person, Care. The Feminist perspective of Miranda Priestly as women in this modern era are Appearance, Experience, and Psychology.